Strategi dan Inovasi Digitalisasi Marketing Pada Bank Syariah Indonesia - Budiani Kusumaningrum; Novi Tri Oktavia; Risqika Yunafiroh; Adi Basuki Choirul; Agus Eko Sujianto (Jurnal Akuntansi dan Pajak, 2023)
This study aims to find out the right strategies and innovations in implementing digital marketing at Bank Syariah Indonesia. This research uses a qualitative approach and a type of case study. To obtain data, researchers used literature studies in the form of books and research articles. The results of the study show that one of the efforts of Islamic banks to increase customer interest is by providing the best digital-based strategy from BSI or Bank Syariah Indonesia. Providing innovation as well as digital-based strategies is the right step in increasing customer interest in placing their funds in Bank Syariah Indonesia. Even though Bank Syariah Indonesia (BSI) is still 2 years old, namely legally operating on February 1, 2021, institutions must continue to innovate in marketing their products digitally. Furthermore, this research shows that Bank Syariah Indonesia is able to innovate with digital marketing designs in the form of Instagram Ads which are the most effective and quickly implemented in society.